Inductive wireless charger - You, Yun. (2010)
This report describes the author‘s final year project in the Info-communications Division of Electrical and Electronic Engineering School in Nanyang Technological University. This project was done in the field of wireless power transfer. It took the transformer’s concept with high frequency signal input which makes the winding coreless. The purpose of the project is to find a way which can provide power to electronic devices without the use of wires. To form the inductive wireless charger, three main parts have been included. The first part is to design the exciting circuit, which provides sufficient input power to the primary charging platform. The exciting circuit is comprised of oscillator circuit and power amplifier circuit. Both of the two circuits have been simulated in software and verified by measurements. The 5W output power can be generated by the exciting circuit. Secondly, a two layer flat primary transmitting planar spiral winding, which is capable of emitting near uniform magnetic field in the near field, was designed. The theoretical supposition was confirmed by measurements and simulations done on Agilent EMDS. Lastly, the Energy-receiving winding and diode rectifier circuit was designed. The single Energy-receiving winding picks up the transfer power from primary side and delivers into diode rectifier circuit. The diode rectifier converts AC power to DC power and supplies the DC power to electronic devices.